2015
DOI: 10.1001/jama.2015.8609
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Characteristics Associated With Penalties in the Centers for Medicare & Medicaid Services Hospital-Acquired Condition Reduction Program

Abstract: year (FY) 2015, the Centers for Medicare & Medicaid Services (CMS) instituted the Hospital-Acquired Condition (HAC) Reduction Program, which reduces payments to the lowest-performing hospitals. However, it is uncertain whether this program accurately measures quality and fairly penalizes hospitals.OBJECTIVE To examine the characteristics of hospitals penalized by the HAC Reduction Program and to evaluate the association of a summary score of hospital characteristics related to quality with penalization in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(136 citation statements)
references
References 23 publications
8
126
0
2
Order By: Relevance
“…[16] Rajaram et al utilized data from the CMS, Center for Disease Control, and Medicare to demonstrate that 721 hospitals were financially penalized by CMS for substandard quality of care in 2015. [34] Those 721 hospitals accounted for 22% of all participating hospitals in the first year of the CMS Hospital Acquired Condition Reduction Program. [34] As healthcare reimbursement continues to transition to a valuebased system that uses standardized care quality metrics to determine reimbursement, it is vital not only to identify disparities in patient care quality but also to enact reforms designed to eliminate these disparities among patients hospitalized with complex and costly diagnoses including primary spinal cord neoplasms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Rajaram et al utilized data from the CMS, Center for Disease Control, and Medicare to demonstrate that 721 hospitals were financially penalized by CMS for substandard quality of care in 2015. [34] Those 721 hospitals accounted for 22% of all participating hospitals in the first year of the CMS Hospital Acquired Condition Reduction Program. [34] As healthcare reimbursement continues to transition to a valuebased system that uses standardized care quality metrics to determine reimbursement, it is vital not only to identify disparities in patient care quality but also to enact reforms designed to eliminate these disparities among patients hospitalized with complex and costly diagnoses including primary spinal cord neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…[34] Those 721 hospitals accounted for 22% of all participating hospitals in the first year of the CMS Hospital Acquired Condition Reduction Program. [34] As healthcare reimbursement continues to transition to a valuebased system that uses standardized care quality metrics to determine reimbursement, it is vital not only to identify disparities in patient care quality but also to enact reforms designed to eliminate these disparities among patients hospitalized with complex and costly diagnoses including primary spinal cord neoplasms. Using a broader and less specific definition of spinal cord neoplasm than the present study, Sharma et al found that the financial burden of spinal cord neoplasms increased significantly during the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…This may be of particular salience to providers that serve medically or socially complex populations, who have been shown previously to perform more poorly on many existing VBP programs, in part because of characteristics of the patients they serve. [21][22][23][24] Transparency for consumers is also a key consideration in the achievement versus improvement debate. If providers are only judged on improvement, a patient viewing a hospital's rating might not know whether a good score was based on high absolute performance or on poor performance with high improvement over time.…”
Section: Rewarding Improvement or Achievementmentioning
confidence: 99%
“…This approach is intended to reward low performers for incremental improvement, but concerns remain that the Medicare programs disadvantage underresourced hospitals and those that serve patients with low socioeconomic status. 55,56 For hospital-acquired conditions, CMS ranks hospitals on the basis of rates of specified complications and will penalize the lowest quartile of hospitals 1% of their Medicare payments in fiscal year 2015. Through the Readmission Reduction Program, CMS will assess penalties of up to 3% of all Medicare payments for hospitals that have higher-thanpredicted risk-adjusted readmission rates for patients hospitalized for pneumonia, heart failure, myocardial infarction, chronic obstructive pulmonary disease, and total knee or hip arthroplasty.…”
Section: Performance-based Payment Incentivesmentioning
confidence: 99%